New horizons in entrepreneurship: from teacher-led to student-centered learning. Issue 7 (8th August 2016) - Robinson, Sarah; Neergaard, Helle; Tanggaard, Lene; Krueger, Norris
Abstract : Purpose: The aim of this paper is to contribute to the discussion about the complexity and heterogeneity of entrepreneurship education. In order to achieve this objective, this paper combines educational psychology with perspectives from entrepreneurship education research to make explicit educators tacit assumptions in order to understand how these assumptions guide teaching. Design/methodology/approach: Using ethnographic analysis, the paper reports data from the continuous development and implementation of a single course over a period of ten years bringing in the educator's and the students perspectives on their achievements and course content. Findings: We find that it is sometimes advantageous to invoke and combine different learning theories and approaches in order to promote entrepreneurial awareness and mindset. It is also necessary to move away from entrepreneurship education as being teacher-led to being more student-centered and focused on experiential and existential lifelong learning practices. Practical implications: Practically, we make suggestions for the design and delivery of a course that demonstrates how four diverse learning theories can be combined to consolidate entrepreneurial learning in students invoking experiential and curiosity based learning strategies. Originality/value: There are very few examples of concrete course designs that have been researched longitudinally in-depth using ethnographic methods. Moreover, most courses focus on the post-foundation period, whereas this paper presents a course that is a primer to the entrepreneurial process and exclusively centered on the pre-foundation phase. Rather than building on a single perspective, it combines a range of theories and approaches to create interplay and progression.